Influence of Metallurgical Slag on the Mechanical Properties of Flexible Pavement - Moncayo Ylma, César Augusto (2023)
The development of transportation infrastructure plays a fundamental role in promoting tourism activities by enhancing the accessibility to various destinations. The quality of paved roads particularly influences the flow of trade and tourism. The research focused on evaluating the influence of the addition of metallurgical slag (MS) to the mechanical properties of flexible pavements. A sample of 60 briquettes underwent testing using the Marshall method with different levels of MS addition: 5 %, 8 %, 12 %, and 15 %. The results revealed that a combination of 4.5 % asphalt content (AC) and 12 % MS proved to be suitable in terms of stability, reaching a value of 1540.3 kg, as well as an average flow of 2.73 cm. Consequently, it is concluded that the inclusion of MS enhances the mechanical properties of the asphalt layer, suggesting that this material could be used in the design of mixtures for road paving. It is recommended that the percentage of MS to be used falls within the range of 5 % to 10 % to maintain an adequate balance between stability and flow in the mixture.